Clinical Outcomes and in vivo Aberrometry Following the Implantation of a Monofocal IOL with Positive Asphericity - van den Berg AB; van den Berg RM; Chamon W; Rocha KM (Clinical Ophthalmology, 2025)
Arthur B van den Berg,1,2 Roberta M van den Berg,1,2 Wallace Chamon,2 Karolinne Maia Rocha1 1Storm Eye Institute, Medical University of South Carolina, Charleston, SC, USA; 2Department of Ophthalmology and Visual Sciences, Federal University of São Paulo, São Paulo, BrazilCorrespondence: Arthur B van den Berg, Department of Ophthalmology and Visual Sciences, Federal University of São Paulo, Rua dos Monjoleiros, 115, Londrina, PR, 86055-744, Brazil, Email arthur-vdb@hotmail.comPurpose: To evaluate ocular aberrations, visual and refractive outcomes in eyes implanted with a monofocal intraocular lens (IOL) with a positive asphericity profile.Patients and Methods: This prospective observational study included 42 eyes (27 patients) that underwent routine cataract surgery and implantation of RayOne EMV monofocal aspheric IOL. PentacamWave was used to assess corneal (at 4.5 and 6.0-mm diameter) and total ocular wavefront aberrations (at 3.0, 3.5, 4.0, and 4.5-mm pupil). Postoperative assessments between 1 and 3 months included manifest and automated refraction, uncorrected and corrected distance visual acuity (UDVA, CDVA), and distance-corrected intermediate and near visual acuity (DCIVA, DCNVA).Results: Postoperatively, UDVA was 0.06 logMAR, with 100% eyes achieving CDVA of 20/25 or better. DCIVA was 0.19 logMAR, with 66.7% of the eyes achieving 20/30 or better. DCNVA was 0.24 logMAR, with 54.8% of the eyes 20/30 or better. Automated refraction measured with various devices revealed myopic results compared to manifest refraction (− 0.24 ± 0.32 D). The mean corneal spherical aberration (4th order) for a 4.5-mm pupil was 0.08 ± 0.06 μm. Total ocular wavefront aberrometry (RMS) showed 0.14 ± 0.04 μm of 4th-order spherical aberration (SA), − 0.03 ± 0.10 μm of 6th-order SA, and 0.12 ± 0.06 μm of coma for a 4.5 mm pupil.Conclusion: In vivo wavefront analysis of eyes implanted with this enhanced monofocal IOL suggests that the IOL’s positive asphericity profile incremented the pre-existing corneal aberrations, leading to useful intermediate and near vision while maintaining distance-corrected visual acuity better than 20/25 in all eyes.Keywords: monofocal IOL, enhanced monofocal IOL, spherical aberration, intermediate vision